Організація поставок союзників за системою ленд-лізу через Іран під час ІІ Світової війни - Фрадинський, Олександр Анатолійович (Університет митної справи та фінансів України, 2015)
Досліджено питання забезпечення поставок військової техніки, стратегічних матеріалів, товарів подвійного призначення, продовольства урядами Великобританії та США для СРСР за системою ленд-лізу через Іран в рамках виконання своїх союзних зобов’язань. Охарактеризовано питання організації митного забезпечення ленд-лізу на ірано-радянському кордоні.

In the article the issue of supply of military equipment and strategic materials, dualuse goods, food and US governments of Great Britain to the Soviet Union for the lend-lease system by Iran within the framework of their union obligations. The analysis of militarypolitical conditions providing the Iranian transit investigated its impact on future military and economic situation on the Soviet-German front. Overview logistical support in issues of Iran's transport infrastructure (ports, roads and railways), replenishment of rolling stock. Characterized question of customs to ensure lend-lease to the Soviet-Iranian border
Keywords: ІІ Світова війна; Іран; США; Великобританія; СРСР; ленд-ліз; вантаж; транспортний коридор; митниця; World War II; Iran; USA; United Kingdom; USSR; the Lend-Lease; cargo; transport corridor; customs